2021
DOI: 10.32598/hdq.6.4.411.3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Relationship Between Occupational Accidents, Work-Family Conflict, and Quality of Work-Life in Emergency Room Nurses

Abstract: Background: This study aimed to model the relationship between occupational accidents, work-family conflict, and quality of work-life in emergency room nurses. Materials and Methods: This correlational research uses path analysis. The study population consisted of all nurses working in the emergency rooms of hospitals in Tehran City, Iran, in 2020. Of them, 200 samples were selected by the available sampling method. To obtain the data, we used the occupational accidents questionnaire, the quality of work-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This finding is in line with several past studies conducted in different settings and geographical jurisdictions (e.g. (Chu et al, 2020;Hefazi Torghabeh et al, 2021)) that mismatch of roles (WFC, FWC) may result in negative work outcomes. For instance, in a study of high-speed railway drivers, Chu et al (2020) also discovered that work-family conflict negatively predicted safety compliance and safety participation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with several past studies conducted in different settings and geographical jurisdictions (e.g. (Chu et al, 2020;Hefazi Torghabeh et al, 2021)) that mismatch of roles (WFC, FWC) may result in negative work outcomes. For instance, in a study of high-speed railway drivers, Chu et al (2020) also discovered that work-family conflict negatively predicted safety compliance and safety participation.…”
Section: Discussionsupporting
confidence: 92%
“…The researchers further reported that high values of WFC significantly correlated to higher rates of personal burnout, and behavioural and cognitive stress symptoms. In such an instance, work-family conflict can play a role in the severity of the relationship between occupational accidents and the quality of safety behaviour (Hefazi Torghabeh et al, 2021). Also, Chu et al…”
Section: Transactional Theory Of Stress and Copingmentioning
confidence: 99%